Treatment outcome and factors associated with mortality due to malaria in Munini District Hospital, Rwanda in 2016–2017: Retrospective cross-sectional study - Hakizayezu, François; Omolo, Jared; Biracyaza, Emmanuel; Ntaganira, Joseph (Frontiers in Public Health, 2022)
Introduction: Malaria is a major public health burden in developing countries in spite of the efforts made by several countries. This disease leads to high morbidity and mortality among Rwandans particularly in the Southern Province where was the sixth national cause of and the first cause of mortality in Munini hospital, but the associated factors remain unknown. Therefore, this study determined the factors associated with deaths among patients with severe malaria to come-up with evidence based interventions to prevent malaria and its factors. Methods: Retrospective cross-sectional study was conducted on malaria patients received in Munini hospital since 2016 to 2017. Data were collected from the patients records or registers who were admitted for severe malaria. Bivariate logistic regression and multivariate hierarchical regression models were conducted based on the odds ratio for assessing the factors associated with deaths. Data were analyzed using the STATA/MP Version.14.1 (Stata Corp 2015, College Station, TX, USA) and Epi-info with proportions. 95% for confidence intervals and 5% for significance levels were ensured. Results:59.1% and 40.9% of malaria patients were females and males respectively. We found 56.25% and 43.75% of deaths in females and males respectively. 78.05% of malaria patients were farmers. Socio-economic and clinical determinants are important predictors for death among patients with severe malaria. Patients with coma had greater odds to die (AOR=7.31, 95%CI:3.33-16.1,p<0.001) than those who were not in coma. Patients who attended consultation after a day had almost 4 times to get died (AOR=3.7, 95%CI:1.8-4.1;p<0.001) compared to those who attended consultation very early. Patients who had severe malaria in dry season were less likely to be died (AOR=0.23, 95%CI:0.08-0.64, p=0.005) compared to those who had severe malaria in rain season. Conclusion: Malaria is an endemic, fatal disease killing when not good treated but also the death still preventable from it when well managed. Comprehensive, long-term, equity-based healthcare interventions and immediate care strategies are recommended.